KONSTRUKSI IDENTITAS SOSIAL “MUSLIMAH MOTIVATIONS RIAU” DALAM GERAKAN HIJRAH MELALUI INSTAGRAM - Rahayu, Titik Endang; Hero, Eko (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
This study aims to find out in-depth about the social construction of "Motivasi Muslimah Riau". This study focused on the construction of social identity "Motivasi Muslimah Riau" in the hijrah movement carried out by the community through Instagram social media. The research method used in this study is a descriptive qualitative approach. The subjects in this study found 7 (seven) informants, consisting of the founders, chairman, secretary, social division, and members obtained through purposive sampling technique. Data collection techniques were carried out through semi-structured interviews, observation, and documentation. The technique of checking the validity of the data is using source triangulation. The theory used in this research is the theory of social construction which is divided into 3 (three) stages, namely externalization, objectivation, and internalization. The results of this study indicate that "Riau Muslimah Motivation" passes through 3 (three) stages in social construction theory, namely externalization, objectivation, and internalization. (1) The stage of externalizing the incident process to Muslim women, the process of forming “Muslimah Motivations Riau” which can make Muslim women aware of covering their genitals, the process of introducing themselves to the community, and the process of adjusting to the vision and mission, as well as administrators and members; (2) at the objectification stage there is a process of interaction through social media and directly, so that there is a process of the interaction process, as well as a process of awareness of position in the community by requiring members to be active and come in every activity; (3) the internalization stage occurs in the process of instilling values ​​and beliefs about the obligation to cover the genitals for Muslim women, changes in members who are aware of covering their genitals according to Islamic law and providing good benefits for the surrounding community